Hidden hunger : strategies to improve nutrition quality - Biesalski, Hans Konrad 1949-; Birner, Regina 1966- (World review of nutrition and dietetics / series editor Berthold Koletzko, 2018)
Hidden hunger has long been an overlooked problem. Vitamin and mineral deficiencies have to be remedied and the availability of calories needs to be increased. As a matter of fact, the number of people who do not have access to a balanced diet has multiplied in rich and poor countries, with lasting consequences for health and well-being. Hidden hunger not only affects childhood growth and cognitive development, but also reduces productivity and well-being later in life, thus keeping the affected population trapped in a circle of poverty and malnutrition. This book illustrates the global fight against hunger by national governments and international organizations. Presented at the Third Hidden Hunger Conference held at the University of Hohenheim in Stuttgart, Germany, it presents a range of strategies being implemented in various regions of the world to improve nutrition quality and combat this international crisis.